Framing terror: A content analysis of media frames used in covering ISIS. (June 2018) - Boyle, Kris; Mower, Jordan
Media organizations all over the world spent a large amount of 2014 covering the influence and activities of the Islamic State in Iraq and Syria (ISIS). This study compares ISIS-related coverage among American, British and Middle Eastern media organizations, identifying the media frames used by these organizations. The findings reveal differences both in the amount of coverage and in the ways that each organization chose to frame its coverage.